PENGARUH FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE DAN INTERNAL LOCUS OF CONTROL TERHADAP FINANCIAL MANAGEMENT BEHAVIOR PADA PELAKU UMKM KOTA SURAKARTA - Sheda, Ghegana Ariel (Politeknik Negeri Ambon, 2023)
This study aims to analyze (1) financial knowledge, (2) financial attitude and (3) internal locus of control on personal financial management behavior in Small and Medium Enterprises in Surakarta City. The population in this study were MSME Entrepreneurs in the Online Shop Marketplace in Surakarta City and the sample in this study amounted to 80 MSMEs in the Online Shop field, the method used was purposive sampling. Based on the results of the t test, financial knowledge does not have a significant effect on financial management behavior in Online Shop MSME actors. The indicators of financial attitude and internal locus of control have a significant influence on the financial management behavior of Online Shop MSME actors. The results of this research can be used as input and reference material for SMEs in overcoming obstacles to financial management when running their entrepreneurship.